(2x-6)(9x+1)=0

Simple and best practice solution for (2x-6)(9x+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-6)(9x+1)=0 equation:


Simplifying
(2x + -6)(9x + 1) = 0

Reorder the terms:
(-6 + 2x)(9x + 1) = 0

Reorder the terms:
(-6 + 2x)(1 + 9x) = 0

Multiply (-6 + 2x) * (1 + 9x)
(-6(1 + 9x) + 2x * (1 + 9x)) = 0
((1 * -6 + 9x * -6) + 2x * (1 + 9x)) = 0
((-6 + -54x) + 2x * (1 + 9x)) = 0
(-6 + -54x + (1 * 2x + 9x * 2x)) = 0
(-6 + -54x + (2x + 18x2)) = 0

Combine like terms: -54x + 2x = -52x
(-6 + -52x + 18x2) = 0

Solving
-6 + -52x + 18x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '2'.
2(-3 + -26x + 9x2) = 0

Factor a trinomial.
2((-1 + -9x)(3 + -1x)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-1 + -9x)' equal to zero and attempt to solve: Simplifying -1 + -9x = 0 Solving -1 + -9x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -9x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -9x = 0 + 1 -9x = 0 + 1 Combine like terms: 0 + 1 = 1 -9x = 1 Divide each side by '-9'. x = -0.1111111111 Simplifying x = -0.1111111111

Subproblem 2

Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3

Solution

x = {-0.1111111111, 3}

See similar equations:

| 5x^4+2x^3=10x^7 | | x^2-3x=1.8 | | 9y^2+z^2=16 | | 4x+x+3x+8x= | | 3(2x-6)=2(6x-3) | | An=xy | | -144/=-16 | | 3.67-6.7x+1.11=22.2 | | -(6xy-10)+2(5xy+8)= | | 5x+6x-3x-5=51 | | (4x^3+4x^2-3x)(x^2-7)=0 | | 5+(3x-3)=3x-(8x-6) | | C-50=28 | | 23=u-10 | | x(3x+2)=8 | | 30x^2-1=5x^2-1 | | x4=1/10 | | 6/7s-5/6s=4/21 | | 15=c/5 | | M+7m+3m-6= | | 2cos^2(2x)-cos(x)=0 | | 2s^2+3s-1=0 | | x^4-y^4-3y^2+1=0 | | -16x^2+75x-51=0 | | -6z=15-7z | | 2cos^2(2x)-cos(2)=0 | | 2x-3(x+3)=23 | | 4k-8=5(k+7) | | 25,200/525 | | x+18-9x=27-6x-9 | | 27=w-35 | | 1x+18-9x=27-6x-9 |

Equations solver categories